Delayed vertebral body collapse after stereotactic radiosurgery and radiofrequency ablation: Case report with histopathologic-MRI correlation. Issue 6 (December 2015) - Wallace, Adam N; Vyhmeister, Ross; Hsi, Andy C; Robinson, Clifford G; Chang, Randy O; Jennings, Jack W
Stereotactic radiosurgery and percutaneous radiofrequency ablation are emerging therapies for pain palliation and local control of spinal metastases. However, the post-treatment imaging findings are not well characterized and the risk of long-term complications is unknown. We present the case of a 46-year-old woman with delayed vertebral body collapse after stereotactic radiosurgery and radiofrequency ablation of a painful lumbar metastasis. Histopathologic-MRI correlation confirmed osteonecrosis as the underlying etiology and demonstrated that treatment-induced vascular fibrosis and tumor progression can have identical imaging appearances.